2021
DOI: 10.3390/su13126791
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Climate-Change Impacts on Energy Efficiency and Overheating Vulnerability of Bioclimatic Residential Buildings under Central European Climate

Abstract: Climate change is expected to expose the locked-in overheating risk concerning bioclimatic buildings adapted to a specific past climate state. The study aims to find energy-efficient building designs which are most resilient to overheating and increased cooling energy demands that will result from ongoing climate change. Therefore, a comprehensive parametric study of various passive building design measures was implemented, simulating the energy use of each combination for a temperate climate of Ljubljana, Slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Most of the regions around the world are experiencing climate change and global warming. A number of researchers have been recently assessing adaptability of passive buildings to climate change in different parts of the world [164][165][166][167][168][169][170][171][172].…”
Section: Climatic Adaptability Of Passive Buildingsmentioning
confidence: 99%
“…Most of the regions around the world are experiencing climate change and global warming. A number of researchers have been recently assessing adaptability of passive buildings to climate change in different parts of the world [164][165][166][167][168][169][170][171][172].…”
Section: Climatic Adaptability Of Passive Buildingsmentioning
confidence: 99%
“…Additionally, previous studies have shown that global warming can significantly influence energy use and thermal comfort conditions in buildings [26][27][28][29]. According to Pajek and Košir [30], the overheating vulnerability of the building stock will have less impact on buildings that have energy-efficient strategies implemented. For example, Haji Ismail et al [27] simulated a prefabricated case study building in the UK and found out that the heating energy use in 2030 and 2080 is estimated to be up to 12% and 34% lower, respectively, than in 2017.…”
Section: Global Warming Impact In Buildingsmentioning
confidence: 99%
“…In another study, Peng et al (2015) found that energy efficiency has a positive effect on CO 2 mitigation in China only in the short term. Pajek and Kosir (2021) argued that increasing the efficiency of energy systems is a way to reduce energy consumption and environmental costs and also a means to achieve resilient energy security. In line with the aforementioned studies, Wu et al (2012), Liimatainen et al (2014), Vieira et al (2018) and Mostafavi et al (2021) have demonstrated the significant positive role of energy efficiency in promoting CO 2 mitigation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2015) found that energy efficiency has a positive effect on CO 2 mitigation in China only in the short term. Pajek and Kosir (2021) argued that increasing the efficiency of energy systems is a way to reduce energy consumption and environmental costs and also a means to achieve resilient energy security. In line with the aforementioned studies, Wu et al.…”
Section: Literature Reviewmentioning
confidence: 99%